Zeolite zsm5-filled pvdf hollow fiber mixed matrix membranes for efficient carbon dioxide removal via membrane contactor - Dasht Arzhandi, Masood Rezaei (American Chemical Society, 2016)
ZSM5 zeolite-filled PVDF mixed matrix membranes were wet spun and used for CO2 absorption in contactor system. The properties of ZSM5 were analytically characterized. SEM images revealed the fully asymmetric structure of membranes, in which the creation of finger-like macrovoids was promoted with the increasing filler loading. A significant increase in gas permeance was observed, which was associated with the porosity increase of the membrane surface despite the decrease in surface pore size. The surface roughness, wettabilite resistance and mechanical stability of membranes were also considerably improved by filler loading. CO2 absorption test with water revealed higher CO2 flux of MMMs than that of the plain membrane. Peak absorption flux of 5.80 × 10-3 molm-2 s-1 was achieved at liquid velocity of 1.2 ms -1 for 5 wt%ZSM5/PVDF membrane(MZ5), which was nearly 177% higher than neat PVDF and also surpassed that of several commercial and in - house made membranes. The mass transfer resistance of the MMMs was also considerably lower than that of PVDF.